Temporal monitoring of subglacial volcanoes with TanDEM-X — Application to the 2014–2015 eruption within the Bárðarbunga volcanic system, Iceland - Rossi, Cristian; Minet, Christian; Fritz, Thomas; Eineder, Michael; Bamler, Richard (Remote Sensing of Environment, 2016)
On August 29, 2014, a lava eruption commenced in the Holuhraun plain, north-east of the Bárðarbunga caldera in Iceland. The eruption ended on February 27, 2015, thus lasting for a period of about 6 months. During these months the magma chamber below the caldera gradually deflated, feeding the eruption and causing the rare event of a slow caldera collapse. In this scenario, TanDEM-X remote sensing data are of particular interest. By producing medium-high resolution and accurate elevation models of the caldera, it is possible to evaluate volume losses and topographical changes to increase the knowledge about the ongoing activity. In particular, five TanDEM-X bistatic acquisitions have been commanded between August 01, 2014 and November 08, 2014, two of them before the volcanic eruption and three of them during the event. Additionally, to fully cover the volcanic activity, the lava field 48 km north-east of the caldera has also been monitored. In the first part of the paper, the expected elevation accuracy is studied on two levels. Absolute and relative height accuracies are analyzed by inspecting the X-band signal propagation into snow and by investigating the impact of the main geometrical system parameters and the local geomorphology. In the second part of the paper, the analysis is applied to the Bárðarbunga volcanic system, including a validation performed using complementary altimeter data. The main geophysical outcome is the accurate temporal height tracking of the entire caldera and the glacial volcanic system. The measured volume loss at the caldera location is about 1 billion cubic meters in two months with an average rate of subsidence of nearly 50 cm/day. These numbers confirm other independent sources and can be compared to lava volume measurements. Finally, the last segment of the dyke that propagated from the Bárðarbunga caldera to the Holuhraun lava field is mapped and a graben structure with a width of up to 1 km and a sinking of a few meters is reported.